The HSP90-RAR1-SGT1 based protein interactome in barley and stripe rust. (July 2015) - Pei, Hongcui; Sun, Quanxi; Hao, Qunqun; Lv, Bo; Wu, Jiajie; Fu, Daolin
Abstract: Protein interactome represents an integrative network governing cellular processes and life activities. The construction of protein interactome is an important step to better understand the whole genome functional genomics. The molecular chaperone complex, HSP90-RAR1-SGT1 (HRS), plays an important role in the R gene-mediated disease resistance in plants. In this study, we aimed to construct the HRS-based protein interactome associated with the barley – Puccinia striiformis f. sp. tritici ( Pst ) pathosystem. Using the yeast two-hybrid (Y2H) approach, we identified fourteen interaction proteins, including nine barley proteins and five Pst proteins. Except for the recapture of HSP90.2, RAR1 and SGT1, the other eleven interactions appeared to be novel, involving the GAF domain containing protein (GAFcp), the heat shock protein 70 (HSP70), the HSP70/HSP90 organizing protein (HOP), the imidazoleglycerol-phosphate dehydratase (IGPD), the pyruvate carboxylase (PC), the short-chain dehydrogenase/reductase (SDR), the tetratricopeptide repeat containing protein (TPRcp), and four unknown proteins. Quantitative real-time PCR (qRT-PCR) analysis revealed that the barley genes HOP, HSP90.1, HSP90.2, RAR1, and SDR were up-regulated during the barley and Pst interaction. Among the Pst genes, HSP70, IGPD, and PC displayed higher expression in mycelia than those in urediospores, but the transcription of GAFcp and PSTG_15777 showed no significant difference between mycelia and urediospores. Taken together, the HRS-based interactome appears to play roles in signaling, metabolism, plant growth, disease resistance, and pathogen invasion. The current study is useful to better understand the HRS-based disease resistance in cereal crops.